Regular patterns of repeated elements in CAD assembly model retrieval. Issue 4 (7th June 2017) - Lupinetti, Katia; Chiang, Lisa; Giannini, Franca; Monti, Marina; Pernot, Jean-Philippe
ABSTRACT: A multitude of online repositories and a large amount of specific CAD model databases are currently available. Therefore, it is crucial to have access to these data in an easy and in a multi-perspective manner according to multiple access keys, not only in terms of annotation data or shape similarity, but also in terms of specific characteristics. In this perspective, this paper proposes a multi-level approach for CAD assembly model retrieval, which exploits assembly specific information related not only to the shape of the constituting components but also to peculiar assembly information, such as kinematic joints and component arrangements. In many cases, most of this information is not explicitly stored, thus tools for its extraction must be provided. In this paper, we focus on the detection of regular patterns of repeated elements in CAD assemblies and on their exploitation for the browsing and retrieval of assembly models. GRAPHICAL ABSTRACT: